Paranetiese deparabolisering van paroesie-gelykenisse by die Sinoptici en die Openbaring aan Johannes - Du Rand, Jan A. (Verbum et ecclesia, 1998)
Paraenetic deparabolization of parousia parables in the Synoptics and the Revelation of John The relevance of the contributions made by the early Christian prophets to the traditions of the Jesus-logia is at stake. When the author of Revelation probably uses Synoptic parable traditions in 2:7; 3:3 and 16:15, he literally transformed it by using the method of paraenetic deparabolization. This was done to apply his message to new receivers in a new situation.